Synthesis of novel ternary hybrid g-C3N4@Ag-ZnO nanocomposite with Z-scheme enhanced solar light‐driven methylene blue degradation and antibacterial activities. Issue 4 (August 2021) - Sher, Mudassar; Khan, Shakeel Ahmad; Shahid, Sammia; Javed, Mohsin; Qamar, Muhammad Azam; Chinnathambi, Arunachalam; Almoallim, Hesham S.
Abstract: We herein report the facile synthesis of ternary hybrid g-C3 N4 @Ag-ZnO nanocomposites (NCs) via a simple physical mixing method. The synthesized g-C3 N4 @Ag-ZnO NCs were successfully characterized using different spectroscopic techniques such as X-Ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscope (TEM), energy dispersive spectroscopy (EDS), Fourier transform infrared (FT-IR), UV-Visible (UV–Vis), steady-state photoluminescence (PL), and electron spin resonance (ESR). Antibacterial performance of the synthesized NCs was evaluated using agar well diffusion assay against Escherichia coli, Bacillus subtilis, Streptococcus salivarius, and Staphylococcus aureus . Moreover, the photocatalytic activity was determined against methylene blue (MB) dye under sunlight irradiation. Results demonstrated that the ternary hybrid g-C3 N4 @Ag-ZnO NCs showed an excellent Z-scheme photocatalytic degradation of MB and significant antibacterial performance against Gram-positive and Gram-negative bacteria as compared to Ag-ZnO nanoparticles (NPs), g-C3 N4 nanosheets (NSs), g-C3 N4 @ZnO NCs and (5%, 10%, 25%, 50%, 60%, and 75%) g-C3 N4 @Ag-ZnO NCs. Moreover, the ternary hybrid g-C3 N4 @Ag-ZnO NCs exhibited tremendous stability and recyclability with a high degree of photocatalytic MB degradation for ten successive catalytic cycles. ESR experiment further revealed that the superoxide ( . O2 − ) and hydroxyl ( . OH) radicals were the leading species liable for MB deterioration. The superior photocatalytic activity and exceptionally improved antibacterial performance of the ternary hybrid g-C3 N4 @Ag-ZnO NCs attributed to the interface's synergic effect developed between Ag-ZnO NPs and g-C3 N4 NSs. Hence, our current study recommends that the synthesized ternary hybrid g-C3 N4 @Ag-ZnO NCs could prove a valuable photocatalytic system for the degradation of organic pollutants and disinfectant for destroying the pathogenic bacterial species from wastewater. Graphical Abstract: ga1 Highlights: g-C3 N4 @Ag-ZnO NCs were synthesized via a simple chemical co-precipitation method. The synthesized g-C3 N4 @Ag-ZnO NCs were successfully characterized. The g-C3 N4 @Ag-ZnO NCs showed an excellent Z-scheme MB photocatalytic degradation. They showed significant antibacterial performance against different bacteria. The g-C3 N4 @Ag-ZnO NCs displayed tremendous stability for ten catalytic cycles.